Building bridges: Connecting sport marketing and critical social science research - Evans, Zachary Charles Taylor; Gee, Sarah; Eddy, Terry (Frontiers in Sports and Active Living, 2022)
Commercial brand involvement in sport has been investigated through multiple lenses; however, in most research, the research questions or problems are addressed using only frameworks from that field of study or its parent discipline, which is often the case in sport marketing. Accordingly, there is an opportunity to ‘de-silo’ the field of sport marketing, and we believe that the field could be advanced by moving towards a more comprehensive examination of brand involvement in sport through purposeful integration of critical social science assumptions, worldviews, and perspectives to examine complex issues in sport. Thus, this paper serves as a starting point for advancing the field of sport marketing in meaningful and impactful ways by offering two research agendas, each accompanied by four actionable recommendations, that could be mutually beneficial in creating new directions for exploring commercial involvement in sport.